High Speed 2: the next government project disaster? - Kyn Aizlewood; Richard Wellings (Institute of Economic Affairs (IEA), 2011)
Challenging the economic case for this white elephantExecutive summary:There is a significant risk that High Speed 2 (HS2) will become the latest in a long series of government big-project disasters with higher-than-forecast costs and lower-than-forecast benefits. HS2 is not commercially viable and will require substantial and increasing levels of subsidy. Taxpayers will therefore bear a very high proportion of the financial risks, which are wholly under-represented in the Economic Case presented by the Department for Transport.The level of financial risk of HS2 is huge, far more than for the earlier HS1 (Channel Tunnel Rail Link). The estimated cost of 34 billion to construct HS2 is equivalent to 1000 per UK income-tax payer. Most taxpayers will derive no benefit from the scheme.The wasteful allocation of resources is demonstrated by the 'gold-plating' of the HS2 route. The first five miles from Euston to Old Oak Common, for example, will add almost 25% (about 4 billion) to the cost of the first phase but deliver negligible time savings.The government's economic case for HS2 depends on estimates of demand growth that are very high compared with a range of previous forecasts for long-distance rail travel. The long timescale adds to the uncertainty surrounding future passenger numbers. A similar approach was taken in forecasting passenger numbers for HS1 and the lessons, clearly reported by the Public Accounts Committee, have not been learned.The economic case for HS2 assumes that time on board a train is wasted for business travellers. In fact many business people are able to undertake productive work during part of their journeys. The economic benefits of HS2 are therefore substantially exaggerated.The construction of the line will involve the appropriation of large numbers of properties on the route. Several areas are likely to be affected by 'planning blight'. Significant environmental and social costs are not included in the assessment of the economic case. Again, painful lessons from HS1, about using existing transport corridors, have not been learned.HS2 is likely to create demand for additional high-cost, taxpayer-funded transport capacity. Terminating the line at Euston may require a new Underground line or Crossrail 2 link to cope with extra passenger numbers.Claims that HS2 will bridge the north-south divide and bring regeneration should be treated with scepticism as the evidence is largely speculative. Alleged benefits must be set against the wider economic losses from the additional taxation required to fund HS2.
Keywords: 330; Rail transport; High-speed rail; Infrastructure investment; Public spending; Great Britain; Schienenverkehr; Hochgeschwindigkeitsverkehr; Infrastrukturinvestition; Öffentliche Ausgaben; Großbritannien